KONTRIBUSI DAYA LEDAK OTOT TUNGKAI DAN KELENTUKAN PERGELANGAN TANGAN TERHADAP KETEPATAN SMASH PADA SISWA YANG MENGIKUTI KEGIATAN EKSTRAKURIKULER BOLA VOLI DI MAN 1 PEKANBARU - Dianri Dwi Putra; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to know the contribution of leg muscle explosive power and flexibility of wrist toward the accuracy of smash at students following extracurricular volley ball activities in MAN 1 Pekanbaru. Population of this research is students following extracurricular volley ball activities in MAN 1 Pekanbaru totaling 20 students. The sampling technique in this research is all of population at extracurricular volley ball activities totaling 20 students. This research use the vertical jump test, flexibilty of wrist test and smash volley ball test. Data analysis techniques in this research use product moment correlation and multiple correlation. The results of this research is there are the contribution of leg muscle explosive power toward the accuracy of smash, with correlation is Rx1y = 0,587 and contribution given is 34,48% with the medium correlation. There is contribution of flexibility of wrist toward the accuracy of smash, with correlation is Rx2y = 0,395 and contribution given is 15,64% with the low correlation. There is contribution of leg muscle explosive power and flexibility of wrist toward the accuracy of smash, with correlation is Rx1x2y = 0,648 and contribution given is 42,04% with the strong correlation.Keywords: Leg muscle explosive power, Flexibility of wrist, Accuracy of smash, Volley Ball